SEARCH FOR THE WAYS AND METHODS OF RESISTANCE TO PUTINISM: UKRAINIAN REALITIES - Grabovska, Iryna (Київський національний університет імені Тараса Шевченка, 2020)
The article examines Putinism as the main conflict-causing factor in the life of the modern Ukrainian community and state. The author analyzed the necessary methods and measures to combat this threat to the existence of an independent Ukrainian state and an independent nation. Based on the study of the latest domestic and foreign analytics and scientific works, the most effective ways of opposing the Putin regime of the Kremlin's newest empire have been identified. It is noted that modern world scientific and popular science analytics is actively engaged in the problems of Putinism, including issues of combating this dangerous phenomenon for the world. The logical conclusions that emerge from these studies are the need for a practical transformation of the "outdated" model of statehood that Putin's Russia is today.Modern Ukraine is a real front in the fight against Putinism, so it should first of all take care of the strategic and tactical directions of the fight against a dangerous enemy. The author emphasizes the need to consolidate the Ukrainian nation around common values: independence, autonomy, freedom, European choice. The article concludes that the joint work of the whole nation to create a civilized, successful country in the political, economic, cultural dimension is needed. In the mass consciousness of Ukrainians, a decisive and unequivocal focus on victory in the war with the Russian aggressor must prevail. Ukraine needs to carry out constant serious analytical and scientific work to study Putinism as a phenomenon. Of great importance for the fight against Putinism is the active defense of the rightness of one's own position in the internal and external arena; struggle against capitulatory sentiments in the middle of Ukrainian society; educating young people in the spirit of Ukrainian effective patriotism; fight against internal problems-threats: corruption, betrayal, irresponsibility of elites, etc.

Досліджено путінізм як головний конфліктогенний фактор у житті сучасної української спільноти та держави. Проведено аналіз необхідних методів та заходів боротьби з вказаною загрозою існуванню української незалежної держави і самостійної нації. На основі вивчення найновішої вітчизняної та зарубіжної аналітики та наукових робіт виявлено най ефективніші напрямки протистояння путінському режиму новітньої імперії Кремля. Відзначено, що сучасна світова наукова та науково-популярна аналітика активно займається проблемами путінізму, у тому числі і питаннями боротьби із цим небезпечним для світу феноменом. Логічні висновки, які витікають із цих досліджень, полягають у необхідності трансформації такої «несучасної» моделі державності, якою є путінська Росія сьогодні.Сучасна Україна є реальним фронтом боротьби з путінізмом, тому їй насамперед варто подбати про стратегічні та тактичні напрямки боротьби з небезпечним ворогом. Авторка наголошує на необхідності консолідації української нації довкола спільних цінностей: незалежності, самостійності, свободи, європейського вибору. Зроблено висновок, що потрібна спільна робота усієї нації по створенню цивілізованої, успішної країни у політичному, економічному, культурному вимірі. Повинна перемогти у масовій свідомості українців рішуча й однозначна орієнтація на перемогу у війні із російським агресором.Потрібно проводити постійну серйозну аналітичну й наукову роботу по вивченню путінізму як феномена. Величезне значення має активне відстоювання правоти власної позиції на внутрішній і зовнішній арені; боротьба з капітулянтськими настроями в середині українського соціуму; виховання молоді у дусі українського дієвого патріотизму; боротьба із внутрішніми проблемами-загрозами: корупцією, зрадництвом, безвідповідальністю, продажністю еліт і утилітаристською обмеженістю мас тощо.
ПОШУКИ ШЛЯХІВ ТА МЕТОДІВ ПРОТИСТОЯННЯ ПУТІНІЗМОВІ: УКРАЇНСЬКІ РЕАЛІЇ
Keywords: Ukraine; Russia; Putinism; conflicts; threats; struggle; timocracy; Praetorian regime; Україна; Росія; путінізм; конфлікти; загрози; боротьба; тимократія; преторіанський режим